Experimental analysis of the effective thermal conductivity enhancement of PCM using finned tubes in high temperature bulk tanks. (September 2018) - Gil, Antoni; Peiró, Gerard; Oró, Eduard; Cabeza, Luisa F.
Highlights: Experimental study at pilot plant scale of addition of fins in LTES systems. Comparison of two LTES tanks, with and without fins, during a charging process. Hydroquinone was selected as PCM. Effective thermal conductivity was compared at different thermal power ratios. Increase in measured thermal effective conductivity was 4.11–25.83% Abstract: Solar cooling is a promising solution to overcome the high energy demand of buildings. Nevertheless, the time dependent nature of the solar source leads to the need of storage systems in order to better match the energy demand and supply. For this purpose, thermal energy storage was considered during last decades as the optimal solution at commercial scale. Latent thermal energy storage offers higher energy densities together with more constant outlet temperature than sensible heat storage, but the low thermal conductivities of PCMs represents the main drawback which limits its applicability. Several studies based on heat transfer enhancement techniques applied in latent thermal energy storage have already been performed. Specifically, the technique of adding fins in storage tanks, which is the most known and studied. However, there are few experimental studies at pilot plant scale focused on this technique and less on the analysis of the heat transfer enhancement through the parameter effective thermal conductivity. This paper presents an experimental study where this parameter is determined and compared using of two identical latent storage tanks, one with 196 transversal squared fins and another one without fins. In this case, hydroquinone was selected as PCM. A set of six experiments was performed at pilot plant of the University of Lleida (Spain), combining three different HTF flow rates and two temperature gradients between HTF inlet temperature and initial PCM temperature. Experimental results showed that the addition of fins can increase the effective thermal conductivity between 4.11% and 25.83% comparing the experiment with highest and lowest thermal power supplied to the PCM, respectively.